Heat kernel estimates and L p -spectral theory of locally symmetric spaces - Weber, Andreas (KIT Scientific Publishing, 2007)
In this work we derive upper Gaussian bounds for the heat kernel on locally symmetric spaces of non-compact type. Furthermore, we determine explicitly the Lp-spectrum of locally symmetric spaces M whose universal covering is a rank one symmetric space of non-compact type if either the fundamental group of M is small (in a certain sense) or if the fundamental group is arithmetic and M is non-compact.
English
Keywords: Laplace-Beltrami-Operator; Wärmeleitungskern; Lokal symmetrischer Raum; Spektrum